2012
DOI: 10.18632/oncotarget.526
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Targets in the Brain Tumor Microenvironment

Abstract: ABSTRACT:Glioblastoma (GBM), a highly malignant brain tumor of adults and children, diffusely invades within the non-neoplastic brain. Despite aggressive current therapeutic interventions, improved therapeutic strategies are greatly needed. Interactions between the tumor and constituents of its microenvironment are known to regulate malignancy, and heparan sulfate proteoglycans (HSPGs) are important as they bind diverse extracellular proteins, including growth factors and cell adhesion molecules, regulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…HS biosynthesis and turnover are strictly regulated processes involving many enzymes interrelated to each other [49,50]. In the course of their synthesis in Golgi, HS chains are elongated by exostosins (EXT1-2).…”
Section: Discussionmentioning
confidence: 99%
“…HS biosynthesis and turnover are strictly regulated processes involving many enzymes interrelated to each other [49,50]. In the course of their synthesis in Golgi, HS chains are elongated by exostosins (EXT1-2).…”
Section: Discussionmentioning
confidence: 99%
“…Proteoglycans, including heparan sulfate and chondroitin sulfate proteoglycans (HSPG and CSPG, respectively), regulate the activity of many signalling pathways, as well as cell–microenvironment interactions. As a result of these diverse functions, proteoglycans and their modifying enzymes have been implicated in tumourigenesis in a number of cancers . In brain cancer, data from our laboratory and other studies suggest that proteoglycans regulate multiple oncogenic pathways in tumour cells and promote critical tumour–microenvironment interactions .…”
Section: Introductionmentioning
confidence: 75%
“…As noted above, the levels of 6O‐sulfation are critical for HSPG function, and altered SULF levels have been associated with a large number of human cancers, including brain, breast, nonsmall cell lung carcinoma, multiple myeloma, gastric, pancreatic cancer and hepatocellular carcinoma . In brain cancer, SULF2 has been directly implicated in driving tumourigenesis in murine and human malignant glioma .…”
Section: Proteoglycans In Cancer Growth Angiogenesis and Inflammationmentioning
confidence: 96%
See 1 more Smart Citation
“…Conversely, the expression of this glypican is up-regulated in hepatocellular carcinomas, although Glypican-3 is not expressed in the liver, suggesting that in this case it behaves as an oncofoetal protein [50]. Recent studies have also showed a downmodulation of Glypican-3 and an up-regulation of Glypican-1 gene expression in glioblastoma [51]. The molecular and immunohistochemical analysis performed in our human CRC set revealed very similar results, indicating the significant association of GPC1 overexpression and GPC3 under-expression in tumor lesions with respect to the normal colon mucosa (Figure 6).…”
Section: Discussionmentioning
confidence: 99%